Predictive Validity and Reliability of Frenchay Activities Index - Li TONG; Shanjia CHEN; Guanli XIE; Cai JIANG; Jing TAO; Lidian CHEN (康复学报)
Objective:To evaluate the reliability and validity of the Chinese version of the Frenchay activities index(FAI)in the recovery period of hospitalized stroke, and to provide evidence for the clinical use of the scale.Methods:The original English FAI was translated and revised according to the international standardized functional assessment of chronic illness therapy(FACIT)principle. An expert review group were formed with four rehabilitation professors, one professor of rehabilitation medicine and one professor of neurorehabilitation psychology, to conduct content validity review for Chinese FAI scale. A total of 403 hospitalized patients from 40 to 80 years old with recovery in five affiliated rehabilitation hospitals, from Huashan Hospital Affiliated to Fudan University, First Affiliated Hospital of Jinan University, Guangdong Provincial Hospital of Traditional Chinese Medicine, Xinjiang Uygur Autonomous Region Chinese Medicine Hospital and Fujian University of Traditional Chinese Medicine, they were assessed by FIA and modified Barthel index(MBI)by face-to-face interviews with the same assessor. The internal consistency, structural validity, project discrimination of the test scale, and the evaluation of the improved Barthel index were used to test the validity of the calibration. Ninety-four subjects were randomly selected within one week and retested by the same assessor.Results:The internal consistency of the Chinese version of the FAI scale was Cronbach's α coefficient of 0.937.The test-retest reliability showed that the intra-group correlation coefficient(ICC)was 0.810(95%CI:0.672 to 0.952).In terms of project discrimination, the differences between the high and low group scores of each project were statistically significant(P<0.01), and the discrimination of each item in the scale was generally good;the correlation analysis of the entries, dimensions and total scores of the Chinese version of the FAI scale found that the correlation coefficient between the items in the Chinese version of FAI and the total score was in the range of 0.535-0.832(P<0.01), and the correlation coefficient of the three dimensions and total scores of household activities, leisure activities and outing activities were 0.867, 0.913, 0.948 respectively(P<0.01).The exploratory factor analysis(EFA)was used to test the structural validity of the Chinese version of the FAI scale to a KMO statistic of 0.924 and the Bartlett spherical χ2test to 4535.558(df=105, P<0.01).Using the principal component analysis method to extract the common factors from the scale, there were three common factors with eigenvalue≥1, the eigenvalue of common factor 1 was 4.776, the contribution rate of variance was 31.842%, and the eigenvalue of common factor 2 was 3.437.The contribution rate of variance was 22.914%, the eigenvalue of common factor 3 was 2.436, the contribution rate of variance was 16.238%, and the cumulative contribution of the three common factors to the total variance was 70.994%.The validity-related validity test showed that the FAI total score was positively correlated with the MBI total score, the correlation was general(r=0.322, P<0.01), and the three dimensions of FAI(home activities, leisure activities, outing activities)was correlated with the MBI total score, the correlation was general(r=0.320, r=0.267, r=0.319, P<0.01).Conclusion:The Chinese version of the Frenchay activities index has good reliability and validity in patients with recovery from stroke hospitalization.